Knowledge On Management Of Side Effects Of Chemotherapy Among Cancer Patients In A Hospital Of Bhaktapur - Shrestha, Sunita (Journal of Manmohan Memorial Institute of Health Sciences, 2023)
Background: Cancer is the second leading cause of death worldwide. The increase in incidence of cancer is directly related to the increase in number of patients receiving chemotherapy. The objective of the study was to assess the knowledge on management of side effects of chemotherapy among cancer patients in a hospital of Bhaktapur. Method: Descriptive cross-sectional study was conducted among 104 cancer patients in a hospital of Bhaktapur, Nepal using non-probability purposive sampling technique. Data was collected through face-face interview technique by using self-developed structured questionnaire. The study was conducted between 2079-10-01 to 2079-10-30. Data management, analysis and interpretation was done using descriptive and inferential statistics and represented in tabulated form. Findings: More than half (56.7%) of the cancer patients had adequate knowledge on management of side effects of chemotherapy. Adequate knowledge was present on management of diarrhoea (82.7%), infection (65.4%) and nausea and vomiting (63.5%). However, inadequate knowledge was present on management of constipation (31.8%), extravasation (33.7%) gums bleeding (35.6%) and hair fall (38.5%). The study shows significant association between level of knowledge on management of side effects of chemotherapy with age (p=0.037) and educational status (p=0.029) of the cancer patients. Conclusion: More than half of the cancer patients had adequate knowledge on management of side effects of chemotherapy. Despite of this, respondents had still gap in knowledge on management of side effects of chemotherapy which shows need for, health education and counselling should be done among cancer patients.